(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Keeping communities clean is becoming increasingly important as technology advances in countries. With the help of technological advancements in all fields and automated segregation methods, it is possible to prevent garbage from piling up. The garbage generated is massive, and the manual labour required to process it is time-consuming. Waste must be systematically regulated to ensure the profitability of the environment. This study used the software development life cycle (SDLC) waterfall model methodology, which includes requirement gathering and analysis, system design, implementation, integration and testing, system deployment, and maintenance, to demonstrate a step-by-step process for achieving the desired problem solution. The researchers surveyed twenty (20) respondents, including ten (10) utility workers and ten (10) barangay officials. Based on the survey results, the researcher concluded that implementing a solar-based garbage segregation system can reduce waste segregation time and worker hazards. It has also received an 85% approval rating from utility workers and barangay officials. This research aims to find a solution to the main problem of improper waste segregation in the selected barangay. This work has a higher potential for waste recovery and reduces occupational hazards for waste separation workers. The researchers proposed a solar-based garbage segregation system using Arduino to implement a waste disposal solution by outfitting a conveyor belt with sensors such as the proximity sensor, ultrasonic sensor, and soil moisture sensor, which detect incoming garbage and activate the servo motor, which classifies it as metal, plastic, or organic waste and deposits it in the appropriate bin. A buzzer, an LCD module, and LED lights are installed to monitor the garbage segregation process.